Intention to quit of employees in private economic sector in the North of Vietnam: A case study of generation X and Y - Uong, Lan Ngoc Thi (International Journal of Innovative Research and Scientific Studies, 2025)
In the context of economic integration and fierce competition, retaining talent and maintaining organizational stability are crucial. This study aims to explore the factors influencing the intention to quit among Generation X and Y employees working in the private sector in northern Vietnam. Data were collected through 455 valid questionnaires and analyzed using quantitative methods such as reliability testing, exploratory factor analysis, correlation analysis, and multivariate linear regression. The results indicate that employees’ intention to quit is directly influenced by personal factors, as well as internal and external factors related to enterprises. These factors, arranged in descending order, include leadership, working conditions, salary and welfare, job satisfaction, job pressure, job fairness, training and promotion opportunities, colleague relationships, attractiveness of other enterprises, organizational commitment, and economic instability. The results of this study offer significant contributions to human resource management activities. Based on the results of the study, several management implications are suggested to assist managers in effectively planning strategies to reduce employee turnover.